Cover Feature: Open Chain Polyarsenides of the Lanthanides (Chem. Eur. J. 31/2018). Issue 31 (8th May 2018) - Schoo, Christoph; Köppe, Ralf; Piesch, Martin; Gamer, Michael T.; Konchenko, Sergey N.; Scheer, Manfred; Roesky, Peter W.
Abstract : An unprecedented intramolecular As‐As coupling, induced by divalent samarium, is depicted on the cover. These are the first complexes of the lanthanides featuring an open chain‐like polyarsenide structure. The coupling takes place within the coordination sphere of polyarsenide transition metal complexes. More information can be found in the Full Paper by S. N. Konchenko, M. Scheer, P. W. Roesky, et al. onpage 7890 .